The Use of Information and Communication Technologies for Households in Statistics of the Years 2010 – 2014. Selected Aspects - SROKA, Mariusz; TABOR, Joanna (Journal of Advanced Research in Management, 2017)
The article presents the results of the research regarding selected aspects of ICT in Polish households in statistics for the years 2010-2014. Particular attention was paid to the number of households possessing computer devices, Internet access as well as to the number of people who regularly use computers. What is more, the paper presents the percentage of Polish households which have broadband Internet access as well as the degree to which individuals use e-government services to search for information, download and send filled forms. The results are compared to the EU-28 average for the selected period of time and to other EU countries in which the above mentioned indices reach the highest and the lowest levels.